1998
DOI: 10.1007/s000110050327
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil adhesion to histamine stimulated cultured endothelial cells is primarily mediated via activation of phospholipase C and nitric oxide synthase isozymes

Abstract: Our results suggest that histamine stimulated neutrophil adhesion is due to H1 and H2 receptor mediated activation of PLC, NOS and GC. Increase of cAMP concentration seems to mediate an inhibitory effect on PMN adhesion to endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Consistent with these reports, we found that cimetidine, an H 2 -histamine receptor antagonist, abolished the increased expresion of PDE4B induced by histamine whilst dexchlorpheniramine, an H 1 -antihistamine, was not effective. H 3 -histamine receptor antagonists were not tested since the existence of this class of histamine receptors on human neutrophils seems unlikely [43,44] In addition, we examined whether the up-regulation by histamine of PDE4 activity in human neutrophils had an impact on their functional responsiveness to a different autacoid, PGE 2 , which also acts by increasing cAMP in human neutrophils following stimulation of EP 2 receptors coupled to adenylyl cyclase [45]. As demonstrated in concentrationresponse studies, pretreatment of cells with histamine substantially decreased the ability of PGE 2 to inhibit the SOZ-induced release of superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these reports, we found that cimetidine, an H 2 -histamine receptor antagonist, abolished the increased expresion of PDE4B induced by histamine whilst dexchlorpheniramine, an H 1 -antihistamine, was not effective. H 3 -histamine receptor antagonists were not tested since the existence of this class of histamine receptors on human neutrophils seems unlikely [43,44] In addition, we examined whether the up-regulation by histamine of PDE4 activity in human neutrophils had an impact on their functional responsiveness to a different autacoid, PGE 2 , which also acts by increasing cAMP in human neutrophils following stimulation of EP 2 receptors coupled to adenylyl cyclase [45]. As demonstrated in concentrationresponse studies, pretreatment of cells with histamine substantially decreased the ability of PGE 2 to inhibit the SOZ-induced release of superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of neutrophils was performed as previously reported (Schaefer et al, 1998) with a slight modification. In short, 24 ml of venous blood was drawn, by venipuncture, from healthy donors into vacutainer tubes (Becton Dickinson, Plymouth, UK) containing 0.11 M sodium citrate and centrifuged at 1500 g for 5 min.…”
Section: Isolation and Preparation Of Calcein-labelled Human Neutrophilsmentioning
confidence: 99%
“…res. 53 (2004) 223 -229 1023-3830/04/060223-07 DOI 10.1007/s00011-004-1246-4 trophil adhesion to endothelial cells [8,9]. These effects have been shown to be mediated by the binding of histamine to specific G-protein-coupled cell surface receptors (GPCR), designated H 1 to H 4 [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%